2018
DOI: 10.1186/s40168-018-0433-4
|View full text |Cite
|
Sign up to set email alerts
|

High salt diet exacerbates colitis in mice by decreasing Lactobacillus levels and butyrate production

Abstract: BackgroundChanges in hygiene and dietary habits, including increased consumption of foods high in fat, simple sugars, and salt that are known to impact the composition and function of the intestinal microbiota, may explain the increase in prevalence of chronic inflammatory diseases. High salt consumption has been shown to worsen autoimmune encephalomyelitis and colitis in mouse models through p38/MAPK signaling pathway. However, the effect of high salt diet (HSD) on gut microbiota and on intestinal immune home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
187
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(216 citation statements)
references
References 66 publications
9
187
4
2
Order By: Relevance
“…HSD, as the substance that comes in direct contact with GI, has been studied for effects on the secretion and function of GI hormones. Research have proven that an 8-week HSD caused both exocrine and endocrine pancreatic insufficiency in rats, which significantly decreased plasma levels of α-amylase and lipase, insulin while significantly increasing TGF-β1 and IL6, resulting in pancreatic fibrosis [26]. An insulin decrease has also been observed with HSD-fed Wistar rats [26,51].…”
Section: Hsd and Gi Hormonesmentioning
confidence: 81%
See 4 more Smart Citations
“…HSD, as the substance that comes in direct contact with GI, has been studied for effects on the secretion and function of GI hormones. Research have proven that an 8-week HSD caused both exocrine and endocrine pancreatic insufficiency in rats, which significantly decreased plasma levels of α-amylase and lipase, insulin while significantly increasing TGF-β1 and IL6, resulting in pancreatic fibrosis [26]. An insulin decrease has also been observed with HSD-fed Wistar rats [26,51].…”
Section: Hsd and Gi Hormonesmentioning
confidence: 81%
“…increased after an HSD [45]. And the study by sequencing the V4 region of 16S ribosomal RNA gene found that HSD increased the Firmicutes/Bacteroidetes ratio, that is, increased the abundances of gen-DOI: 10.1159/000493096 era Lachnospiraceae and Ruminococcus (p < 0.05) but decreased the abundance of Lactobacillus (p < 0.05) [26]. As the onset of Lactobacillus depletion is quick and remarkable, the Lactobacillus murinus is the most strongly associated with HSD [46].…”
Section: Hsd Alters the Gut Microbiota Profilingmentioning
confidence: 97%
See 3 more Smart Citations